2021
DOI: 10.26493/1855-3974.2554.856
|View full text |Cite
|
Sign up to set email alerts
|

On complete multipartite derangement graphs

Abstract: Given a finite transitive permutation group G ≤ Sym(Ω), with |Ω| ≥ 2, the derangement graph Γ G of G is the Cayley graph Cay(G, Der(G)), where Der(G) is the set of all derangements of G. Meagher et al. [On triangles in derangement graphs, J. Combin. Theory Ser. A, 180:105390, 2021] recently proved that Sym(2) acting on {1, 2} is the only transitive group whose derangement graph is bipartite and any transitive group of degree at least three has a triangle in its derangement graph. They also showed that there ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Conjectures 1.1(ii) and (iv) were settled, respectively, in [6] and [17]. Furthermore in [6] it was shown that I 2p = {1, 2} for every odd prime p and a complete characterization of groups of degree 2p with intersection density 2 was also given there.…”
Section: Introductory Remarksmentioning
confidence: 99%
“…Conjectures 1.1(ii) and (iv) were settled, respectively, in [6] and [17]. Furthermore in [6] it was shown that I 2p = {1, 2} for every odd prime p and a complete characterization of groups of degree 2p with intersection density 2 was also given there.…”
Section: Introductory Remarksmentioning
confidence: 99%
“…For arbitrary transitive groups, however, intersecting sets can have size larger than the order of a stabilizer of a point and the maximum intersecting sets can have a more complex structure than the canonical intersecting sets (see [25] for instance). The smallest example of transitive groups (both in terms of order and degree) whose maximum intersecting sets have size larger than the order of stabilizer of a point is the alternating group Alt(4) acting on the 2-subsets of {1, 2, 3, 4} (see [29]).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, if ρ(G) = k > 1, then the largest intersecting set of G has size k times the order of a point stabilizer of G (i.e., the size of the canonical intersecting sets). Several papers on the intersection density of transitive groups have recently appeared in the literature [17,18,19,22,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Following [12] we define I n to be the set of all intersection densities of transitive permutation groups of degree n, that is, Conjecture 1.2 is settled in [13], where an additional problem regarding the possible values of intersection densities in I 2p was posed.…”
Section: Introductory Remarksmentioning
confidence: 99%